Strategi Kebijakan Keuangan dan Fiskal Untuk Meningkatkan Kesejahteraan Masyarakat - M.Fadhil Royhan; Valen Zikra; M.Zulfikri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article explores the strategic implementation of financial and fiscal policies aimed at enhancing community welfare. It begins by defining key concepts and the importance of sustainable economic growth for societal well-being. The study highlights the role of government spending and taxation in redistributing resources to underserved populations. By analyzing case studies from various countries, the article illustrates successful policy frameworks that have led to improved living standards. Furthermore, it discusses the challenges policymakers face in balancing economic efficiency with equity. The significance of stakeholder engagement in policy formulation is also emphasized, showcasing how community input can lead to more effective outcomes. Additionally, the article examines the impact of social safety nets and public services on reducing poverty and inequality. It advocates for a holistic approach that integrates both financial and fiscal measures to create a comprehensive strategy for welfare enhancement. Ultimately, the findings suggest that well-designed policies can significantly improve the quality of life for all citizens. The article concludes with recommendations for future research and policy development aimed at fostering inclusive growth.